Arguing to Agree: Mitigating My-Side Bias Through Consensus-Seeking Dialogue. (July 2015) - Felton, Mark; Crowell, Amanda; Liu, Tina
Research has shown that novice writers tend to ignore opposing viewpoints when framing and developing arguments in writing, a phenomenon commonly referred to as my-side bias. In the present article, we contrast two forms of argumentative discourse conditions (arguing to persuade and arguing to reach consensus) and examine their differential effects on my-side bias in writing. Our data reveal that when asked to write an essay to support their opinions on capital punishment, individuals who had argued to reach consensus were more likely to cite claims that challenge their position, reconcile these claims with their position, and make use of claims that had originally been introduced by their dialogue partners. We discuss these findings in light of educational policy and practice and caution against an overemphasis on using persuasive discourse as a means of teaching argumentative reasoning and writing.